Strategic Sensemaking and Organizational Performance: Linkages Among Scanning, Interpretation, Action, and Outcomes - Thomas, James B.; Clark, Shawn M.; Gioia, Dennis A. (Academy of Management Journal, 1993)
This study investigated the strategic ?sensemaking? processes of scanning, interpretation, and action and how those activities are linked to organizational performance. Using path analyses on data from 156 hospitals, we tested the direct and indirect effects among these sensemaking processes and performance outcomes and developed a model of their relationships. In a more general sense, the research represents an attempt to provide insight not only into relationships between cognition and action, but also into the links between those fundamental processes and organizational performance outcomes.